Children With Dyslexia and Typical Readers: Sex-Based Choline Differences Revealed Using Proton Magnetic Resonance Spectroscopy Acquired Within Anterior Cingulate Cortex - Horowitz-Kraus, Tzipi; Brunst, Kelly J.; Cecil, Kim M. (Frontiers in Human Neuroscience, 2018)
Children with dyslexia exhibit slow and inaccurate reading, as well as problems in executive functioning. Decreased activation in brain regions related to visual processing and executive functioning has been observed with functional magnetic resonance imaging. However, the underlying neurochemistry has not been thoroughly evaluated. Reading ability and executive functioning were assessed in fifty-three children (8-12 years old, dyslexia (n=30) and typical readers (n=23)). Tests of Word Reading Efficiency to assess the participant’s ability to pronounce printed words (sight word efficiency) and Tests of Silent Reading Efficiency and Comprehension were included in the reading ability battery. We employed short echo, single voxel, proton magnetic resonance spectroscopy to evaluate the anterior cingulate cortex. Logistic regression models were used to determine the independent effects of brain metabolite levels and reading ability on dyslexic status (yes/no). While we did not observe significant main effects of brain metabolite levels on dyslexic status, the effect of N-acetyl aspartate on dyslexia status is significantly modified by word reading efficiency, particularly sight word efficiency, in adjusted models (P NAA*TOWRE_SWE=0.046). Participants with higher N-acetyl aspartate levels and lower sight word efficiency have greater probability of being dyslexic compared to typical readers. Similarly, participants with higher Choline levels and lower silent reading efficiency and compression have a significantly (P Cho*TOSREC=0.02) greater probability of being dyslexic compared to typical readers. These findings suggest that metabolite changes associated with atypical cellular density in the anterior cingulate cortex may be present in children with dyslexia, and may be used as possible markers for dyslexia.